Dolichogenidea sp. (Hymenoptera : Braconidae) - a Parasitoid of Locastra muscosalis Walker (Lepidoptera : Pyralidae) - Sharma, Ajay; Verma, T. D. (Indian Forester, 2007)
Locastra muscosalis Walker (Lepidoptera : Pyralidae) is a serious pest of Pistacia, Apple and Poplars. Larvae of this pest make the webs by uniting the leaves together with the help of silken threads secreted by Lannea grandis and feed voraciously on the leaves of host trees while living inside these webs. The damage caused by this insect is upto an extent that some times the whole tree is defoliated and it is not able to bear the leaves for the remaining season. During the biological study of this pest an egg larval parasitoid has been found to kill this pest. The parasitoid has been identified as Dolichogenidea sp. The parasitoid larva come out of the host body and make a white cocoon before pupation. The adults were black in colour and having transparent wings. The detailed biology of the parasitoid is presented.